A study of the product styling design evaluation system and applications for handheld transceivers. (3rd October 2017) - Chen, Hui; Tan, Yong-Sheng; Song, Wu
Abstract: This study is based on the fundamental contents and program of product styling designs. Embodied individual properties of handheld transceiver products and styling design experiences were integrated into the investigation. Via detailed questionnaire investigations and data analyses, the contents of evaluating handheld transceiver product design schemes can be verified and confirmed. This approach follows both fundamental quantitative and qualitative principles including comprehensiveness, systematicness, and flexibility. An evaluation model for the product styling of handheld transceivers has been built along and subjective factors, neutral factors, and objective factors serve as the factors of the first-level indicators. The analytic hierarchy process was used to build the hierarchical structure of the evaluation system. The sum-product method was utilized to calculate the weight vectors in order to form the ranking of levels in the hierarchy. The weight index of each level of the hierarchy in the evaluation system can also be obtained. The final step is to implement the examination and verification of this design evaluation system on the product styling designs for handheld transceivers. The implementation verified the objectivity, rationality, and effectiveness of this evaluation system, which has been endorsed jointly by enterprise customers and design houses. This approach has been verified to be provided with economic values and social values to a certain extent.